Evaluación del estado nutricional y riesgo cardio metabólico en escolares de la Unidad Educativa 23 de abril del Cantón Guaranda. Noviembre 2023 – abril 2024. - Peña Galarza, Jessica Anahy (2024)
Overweight and obesity increasingly affect the population of all ages and are considered an emerging epidemic. Objective: determine the relationship between nutritional status and cardio-metabolic risk in school children of the April 23 Educational Unit of the Guaranda canton. Methodology: this research is field, non-experimental, descriptive, cross-sectional correlational, based on scientific theories where data were collected by measuring weight, height and waist circumference, subsequently a database was created where the index of body mass individually, which was compared with the reference values of the World Health Organization and the cardiometabolic risk was determined by means of the waist-height ratio. Results: The sample consisted of 75 schoolchildren, of which (55%) of the students were male and (45%) were female. The nutritional status showed that there was a greater predisposition to overweight (14.71%) in females than in males (2.44%); obesity represented (5.88%) in females and severe obesity (2.44%) in males. The cardio-metabolic risk determined that there is a predisposition to present cardio-metabolic risk in females (8.82%) than in males (4.88%). Conclusion: It is determined that in the studied population there